I do solemnly swear : the moral obligations of legal officials - Sheppard, Steve, 1963- (Cambridge University Press, 2009)
What should the people expect from their legal officials? This book asks whether officials can be moral and still follow the law, answering that the law requires them to do so. It revives the idea of the good official - the good lawyer, the good judge, the good president, the good legislator - that guided Cicero and Washington and that we seem to have forgotten. Based on stories and law cases from America's founding to the present, this book examines what is good and right in law and why officials must care. This overview of official duties, from oaths to the law itself, explains how morals and law work together to create freedom and justice, and it provides useful maxims to argue for the right answer in hard cases. Important for scholars but useful for lawyers and readable by anybody, this book explains how American law ought to work.